2021
DOI: 10.3389/fcell.2021.633035
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment With Everolimus, an mTOR-Specific Antagonist, or Downregulation of ELK1 Enhances the Sensitivity of Pancreatic Cancer Cells to Genistein

Abstract: Genistein is a natural isoflavone with pharmacological or potentially anti-tumor properties. However, the resistance of cancer cells to genistein remains a major obstacle. This study focused on the mechanism implicated in the resistance of pancreatic cancer (PC) cells to genistein and the mechanism of action. First, key molecules and signaling pathways related to genistein resistance in PC cells were explored using bioinformatics tools. DEP domain containing MTOR interacting protein (DEPTOR), a typical inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Subsequently, the mice were euthanized by intraperitoneal injection of an overdose of pentobarbital sodium (150 mg/kg) [ 14 ]. Successful animal death was confirmed by the loss of corneal and nerve reflexes with noticeable pupil dilation, the absence of respiration, pulse, and heartbeat for more than 5 min, and the possibility of simple cardiac arrest was excluded [ 15 ]. Subsequently, their hearts and blood samples were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the mice were euthanized by intraperitoneal injection of an overdose of pentobarbital sodium (150 mg/kg) [ 14 ]. Successful animal death was confirmed by the loss of corneal and nerve reflexes with noticeable pupil dilation, the absence of respiration, pulse, and heartbeat for more than 5 min, and the possibility of simple cardiac arrest was excluded [ 15 ]. Subsequently, their hearts and blood samples were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, animal studies have verified that AXP107-1 in combination with gemcitabine has synergistic anti-cancer effects by activating GPER1 signaling [217]. In addition, Li et al [218] showed that downregulation of ELK1 leads to upregulation of DEPTOR, which in turn enhances the sensitivity of PC cells to genistein through inhibition of mTOR signaling [218]. The anti-cancer effects of genistein in vitro are associated with induction of ROSmediated mitochondrial apoptosis, cell cycle arrest, and regulation of STAT3 signaling [219].…”
Section: Genisteinmentioning
confidence: 99%